Improving heat resilience in fattening rabbits: nutritional strategies for mitigation via regulating blood physiology, inflammation and antioxidant pathways - Khaleel, Hadeel Kamil; Abdelnour, Sameh A.; Osailan, Raha; El-Kholy, Khaled H.; El-Haroun, Ehab; El-Nagar, Hamdy A.; Mehilp, Sara T.; El-Raghi, Ali A.; Hassan, Mahmoud A.; Moustafa, Mahmoud; El-Ratel, Ibrahim T. (Frontiers in Veterinary Science, 2025)
IntroductionGlobal heat waves increasingly threaten food security, by reducing food supplies and negatively impacting livestock health. This research investigates nutritional interventions aimed at improving rabbit productivity and health, with a particular focus on mitigating the effects of heat stress (HS) conditions. Hence, this research investigates the potential of various feed additives to enhance growth, immunity, and overall health in environmentally stressed growing rabbits by reducing inflammatory and apoptotic signaling.Materials and methodTo investigate the effects of various supplements on rabbits under natural heat stress, 150 rabbits were divided into five groups with 30 rabbits each. The groups were given a control diet or supplemented with 1 ml of silver nanoparticles (AgNPs), 0.2 g of chitosan, 100 mg of silymarin, or a combination of all three for 8 weeks. The Temperature-Humidity Index (THI) was calculated to be 30.04, indicating severe heat stress.ResultsResults indicated that all feed supplements significantly improved live body weight and average daily gain (p < 0.05). The inclusion of dietary feed additives resulted in significant elevations in total protein (p < 0.01), albumin (p < 0.001), hemoglobin (Hb) (p < 0.01), and red blood cell (RBC) counts (p < 0.012) relative to the control diets. Conversely, dietary supplementation significantly attenuated serum concentrations of aspartate aminotransferase (AST; p < 0.001), triglycerides (TG; p < 0.001), total cholesterol (TC; p < 0.001), very-low-density lipoprotein (VLDL) (p < 0.001), urea (p = 0.04), and creatinine (p = 0.008) in comparison to the heat stress group. Administration of dietary supplements resulted in statistically significant elevations in total antioxidant capacity (p = 0.0032), glutathione (p = 0.002), catalase (p < 0.001), and glutathione peroxidase (p < 0.001), alongside a significant reduction in serum malondialdehyde (p = 0.0007), when compared to the control group. Similarly, these dietary interventions significantly enhanced overall immune ability, with increased IgM (p < 0.001), IgA (p = 0.0059), phagocytic activity (p < 0.001), and complement component 3 (C3) (p < 0.001). In addition, rabbits receiving dietary supplements displayed significantly reduced serum concentrations of pro-inflammatory cytokines, specifically tumor necrosis factor alpha (TNF-α, p = 0.0091), Interleukin 4 (IL-4, p = 0.0004), and interferon gamma (IFN-γ, p = 0.0211), compared with the stressed control group. Histopathological examination of liver tissues provided further evidence that all tested feed additives enhanced overall hepatic health.ConclusionTherefore, incorporating mixture of natural molecules (1 ml AgNPs, 0.2 chitosan, and 100 mg silymarin) into the diet provides a sustainable and promising solution for rabbit production to combat heat stress associated with global climate change.